The influence of brand trust on customer purchase behavior : Mediating digital interactions on instagram - Pane, Angelina; Fernando, Yudi; Ikhsan, Ridho Bramulya; Mergeresa, Fineke; Fernando, Erick; Prabowo, Hartiwi (Institute of Electrical and Electronics Engineers Inc., 2024)
Instagram as a form of social media has brought about favorable consequences for businesses owing to the role played by user engagement. Consequently, businesses make use of Instagram as a means to enhance the trust consumers have in their brand. Nevertheless, users encounter numerous challenges when engaging with Instagram to purchase products. The present study examines the correlation between perceived relative advantages and the trust consumers place in digital interaction and their purchasing behavior about nutritional supplement products on Instagram. Empirical data was gathered from an online survey of 162 Instagram users who had previously purchased nutritional supplement products through the platform. The research hypotheses were tested using multivariate analysis with component-based structural equation modeling. The findings of this study reveal a positive and statistically significant impact of perceived relative advantages and brand trust on digital interaction. Furthermore, brand trust and digital interaction were found to positively and significantly impact purchasing behavior. However, perceived relative advantages were not found to impact purchasing behavior significantly. Consequently, this study has provided valuable insights for businesses seeking to utilize Instagram to enhance the purchasing behavior of nutritional supplement products.